SEVOFLURANE, DESFLURANE, AND XENON NEW INHALED ANESTHETICS IN VETERINARY MEDICINE - Natalini,Cláudio Correa (2001)
Inhalation anesthesia is widely used in veterinary medicine. New inhalation anesthetics that present less untoward effects, are more potent and produce a safe and easily changeable anesthetic plane are desirable over the older agents presently available. In this review some of the physical and chemical aspects of inhalation anesthesia is revisited. Because the agents used in inhalation anesthesia are gases or vapors, the physics of vaporization, delivery and administration of these agents should be understood. The two new inhalation anesthetics sevoflurane and desflurane, and the new anesthetic gas xenon have been used in human beings for some time. In veterinary medicine there is a lack of investigation and reports that assure the safety and clinical aspects of using them in animals. The information available on the use of these new agents in animals is revised in this article.